Co-adaptive Training Improves Efficacy of a Multi-Day EEG-Based Motor Imagery BCI Training - Abu-Rmileh, Amjad; Zakkay, Eyal; Shmuelof, Lior; Shriki, Oren (Frontiers in Human Neuroscience, 2019)
Motor imagery (MI) based brain computer interfaces (BCI) detect changes in brain activity associated with imaginary limb movements, and translate them into device commands. MI based BCIs require training, during which the user gradually learns how to control his or her brain activity with the help of feedback. Additionally, machine learning techniques are frequently used to boost BCI performance and to adapt the decoding algorithm to the user's brain. Thus, both the brain and the machine need to adapt in order to improve performance. To study the utility of co-adaptive training in the BCI paradigm and the time scales involved, we investigated the performance of 18 subjects in two groups, in a 4-day MI experiment using EEG recordings. One group (control, n=9 subjects) performed the BCI task using a fixed classifier based on MI data from day 1. In the second group (experimental, n=9 subjects), the classifier was regularly adapted based on brain activity patterns during the experiment days. We found that the experimental group showed a significantly larger change in performance following training compared to the control group. Specifically, although the experimental group exhibited a decrease in performance between days, it showed an increase in performance within each day, which compensated for the decrease. The control group showed decreases both within and between days. A correlation analysis in subjects who had a notable improvement in performance following training showed that performance was mainly associated with modulation of power in the $α$ frequency band. To conclude, continuous updating of the classification algorithm improves the performance of subjects in longitudinal BCI training.